2009
DOI: 10.1109/jqe.2009.2027446
|View full text |Cite
|
Sign up to set email alerts
|

Optical Parabolic Pulse Generation and Applications

Abstract: International audienceParabolic pulses in optical fibers have stimulated an increasing number of applications. We review here the physics underlying the generation of such pulses as well as the results obtained in a wide range of experimental configurations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 86 publications
1
56
0
Order By: Relevance
“…The use of nonlinear propagation in fiber to create parabolic-shaped pulses has been extensively studied in the literature, with an emphasis on fiber amplifiers [43,44]. An arbitrary pulse inserted in an active (gain) or dispersion-decreasing fiber (where a longitudinal decrease of the normal dispersion emulates linear gain) is nonlinearly attracted toward an asymptotically evolving parabolic pulse subject to certain relations (scaling) between pulse amplitude, duration and chirp parameter.…”
Section: Generation Of Nearly Transform-limited Parabolic Pulses Of Pmentioning
confidence: 99%
“…The use of nonlinear propagation in fiber to create parabolic-shaped pulses has been extensively studied in the literature, with an emphasis on fiber amplifiers [43,44]. An arbitrary pulse inserted in an active (gain) or dispersion-decreasing fiber (where a longitudinal decrease of the normal dispersion emulates linear gain) is nonlinearly attracted toward an asymptotically evolving parabolic pulse subject to certain relations (scaling) between pulse amplitude, duration and chirp parameter.…”
Section: Generation Of Nearly Transform-limited Parabolic Pulses Of Pmentioning
confidence: 99%
“…Indeed, it has been demonstrated that any initial waveform propagating under conditions of normal dispersion, non-linearity and distributed gain will evolve asymptotically into a similariton, a pulse characterized by a parabolic intensity profile with a linear positive chirp [30][31][32] . Once this typical parabolic profile is obtained, it propagates self-similarly, i.e.…”
Section: Principle Of Operation and Configuration Under Studymentioning
confidence: 99%
“…3(a) the temporal intensity profiles after the nonlinear propagation in the passive or active HNLF and before spectral filtering (initial pulses having the initial power corresponding to the working points of the regenerator). The output pulse shape exhibit marked differences : the pulses obtained after propagation in the RFA clearly exhibits the parabolic signature 31,32) . On the contrary, in the passive fiber, the temporal profile is flattened as can be obtained after the wavebreaking stage 33) and which has been found to be crucial for MR behavior 11) .…”
Section: Pulse Dynamics In a Simplified Model With Constant Distributmentioning
confidence: 99%
“…The amplitude and width scaling in this case depend only on the amplifier parameters and input pulse energy. Parabolic pulses have found numerous applications in pulse amplification and compression 7 as well as in optical communications. 5,7 These include optical regeneration, 8 pulse re-timing, 9 the optimization of return-to-zero optical receivers, 10 and mitigation of linear waveform distortions.…”
Section: Introductionmentioning
confidence: 99%